Physical dry recovery method for positive plates of waste lithium iron phosphate batteries
By combining low-temperature freezing embrittlement with multi-stage mechanical sorting and porous ceramic roller adsorption, the problems of difficult removal of binders and low separation rate in the recycling of lithium iron phosphate battery cathode sheets have been solved, achieving efficient and environmentally friendly separation of black powder and aluminum foil, and achieving high purity and high recovery rate.
Patent Information
- Application Number
- CN202511132549.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-13
- Publication Date
- 2025-11-11
AI Technical Summary
Existing methods for recycling lithium iron phosphate battery cathode sheets suffer from problems such as the generation of toxic gases due to high-temperature roasting, difficulty in removing binders, and low separation rates. Furthermore, traditional mechanical methods cannot effectively remove PVDF binders.
The process employs a combination of low-temperature cryogenic embrittlement treatment, multi-stage mechanical sorting, and porous ceramic roller adsorption. PVDF is embrittled at low temperature using liquid nitrogen, followed by melting of PVDF with pulsed hot air and directional adsorption using porous ceramic rollers. Finally, airflow sorting is used to achieve efficient separation of black powder and aluminum foil.
It achieves high-purity (over 99%) and high-yield (over 95%) separation of black powder and aluminum foil, avoiding chemical pollution and high-temperature damage, and providing a high-value recycling pathway.
Smart Images

Figure CN120920462A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery electrode recycling technology, specifically to a method for the physical dry recycling of waste lithium iron phosphate battery positive electrode sheets. Background Technology
[0002] Lithium iron phosphate (LFP) batteries are widely used in new energy vehicles and energy storage due to their safety and low cost. However, with the large-scale deployment of these batteries, the issue of obsolescence has become prominent. Their actual lifespan is relatively short (approximately 4-6 years), and they are retired when their capacity decays to 80%. Furthermore, their manufacturing process generates 3-5% waste. Improper disposal can pollute water and soil, harm the ecosystem and health, and waste resources such as lithium and aluminum. With the expansion of new energy vehicles, the demand for these resources is surging, leading to significant supply pressure. Recycling spent LFP batteries can alleviate the shortage, reduce reliance on primary mineral resources, create economic benefits, and is an essential requirement for sustainable development.
[0003] The recycling of lithium iron phosphate battery cathode sheets mainly involves separating black powder, aluminum foil, and binders. Currently, commonly used recycling methods for lithium iron phosphate battery cathode sheets include wet recycling, pyrolysis recycling, and traditional mechanical recycling, but all have significant limitations: wet recycling uses organic solvents such as N-methylpyrrolidone (NMP) to remove binders, resulting in high processing costs and difficulty in removing residual organic solvents; pyrolysis uses high-temperature roasting at 500-600℃ to thermally decompose the binder, producing toxic fluorine-containing gases that are difficult to treat, and high-temperature roasting also alters the lattice structure of lithium iron phosphate, making it difficult to reuse; traditional mechanical separation relies solely on mechanical crushing, which cannot effectively remove PVDF binders, resulting in low separation rates of black powder and aluminum foil. Summary of the Invention
[0004] To address the aforementioned technical problems, a method for the physical dry recycling of waste lithium iron phosphate battery cathode sheets is provided. This invention employs low-temperature freezing to facilitate the peeling of the binder. After multi-stage mechanical sorting, hot air melts the binder, which is then directionally adsorbed and captured by porous ceramic adsorption rollers. Subsequent airflow sorting enables the physical dry recycling of black powder and aluminum foil with a purity of over 99% and a yield of over 95%.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solution:
[0006] The method for physical dry recycling of spent lithium iron phosphate battery cathode sheets includes the following steps:
[0007] S1. After fragmentation treatment of waste lithium iron phosphate battery positive electrode sheets, electromagnetic sorting is used to remove ferromagnetic impurities, forming electrode sheet fragments.
[0008] S2. The electrode fragments are subjected to low-temperature embrittlement treatment to form embrittled electrode fragments; low-temperature freezing causes the PVDF polymer binder to undergo a glass transition, and the peeling force is reduced after embrittlement.
[0009] S3. Perform a first-stage mechanical dissociation process on the embrittled electrode sheet to obtain granular electrode sheets with a particle size of less than 2 mm. During the first-stage dissociation, due to the previous freezing embrittlement, the interfacial forces between the binder and the black powder, and between the binder and the current collector are weakened and partial peeling occurs. In order to further completely peel off the three, a subsequent second-stage mechanical dissociation process is performed. Then, the second-stage mechanical dissociation process is performed to obtain the dissociated material.
[0010] S4. The dissociated material is subjected to two-stage sieving to obtain oversize, intermediate and undersize. The oversize consists of coarse agglomerated particles larger than 300 micrometers, the undersize consists of fine black powder smaller than 50 micrometers, and the intermediate has a particle size of 30-300 micrometers. The fine black powder mainly includes black powder, polymer binder and trace current collector. The coarse particles are returned to the secondary mechanical dissociation process for recycling.
[0011] S5. The fine black powder is fed into a hollow porous ceramic roller from one end via an airflow. A pulsed hot air stream is used to heat the fine black powder at the feed inlet of the porous ceramic roller. The pulsed hot air melts the polymer binder in the fine black powder. The molten polymer binder is then adsorbed by the micropores of the porous ceramic roller and expelled from the roller. These micropores extend to the outside of the roller, thereby removing and recovering the polymer binder, resulting in a mixture of black powder and a current collector. The pulsed hot air can melt the binder to be processed in a short time, which is then adsorbed by the porous ceramic roller, preventing the binder from being subjected to prolonged high-temperature heating. Thermal decomposition and prevention of damage to the black powder lattice structure; pulsed hot air has a certain impact effect, which can promote the separation of binder and black powder; pulsed hot air mainly heats the binder and is not used continuously, reducing energy consumption; the micropores of the porous ceramic roller are used for directional adsorption of molten polymer binder (PVDF). The principle is that the surface energy of molten PVDF is close to that of ceramic, while the surface energy of black powder is higher. Therefore, PVDF is more easily adsorbed by the micropores of the ceramic roller. After PVDF melts, it becomes a fluid and can be deformed and squeezed into the micropores, while black powder cannot overcome the energy barrier to enter the micropores due to its high surface energy.
[0012] S6. Perform airflow separation on the mixed materials to separate black powder and current collector debris.
[0013] Furthermore, the area of the electrode fragment does not exceed 25 cm². 2 The magnetic separation intensity of the electromagnetic separation is at least 2000 GS.
[0014] Furthermore, the low-temperature embrittlement treatment is performed at ambient temperature (-25°C to -60°C) under normal pressure for 30-60 seconds. The ambient temperature is controlled by adjusting the flow rate of refrigerant gases such as liquid nitrogen.
[0015] Furthermore, the primary mechanical dissociation process employs a toothed disc crusher, with the speed of the toothed disc crusher ranging from 500 to 1500 rpm.
[0016] Furthermore, the secondary mechanical dissociation process employs a vortex mill to refine the particle electrode to a particle size of 300 micrometers or less; the mechanical rotation speed of the vortex mill is 2000-4000 rpm, and the mechanical grinding time is 30-120 seconds. The vortex mill mechanical grinding can grind the current collector, black powder, and binder into powder, at which point the black powder, binder, and current collector have been separated.
[0017] Furthermore, the polymeric adhesive is polyvinylidene fluoride (PVDF); the temperature of the pulsed hot air is 190-220℃, and the wind speed is in the range of 10-30 m / s; the outer surface temperature of the porous ceramic roller is 160-185℃, and the roller speed of the porous ceramic roller is in the range of 5-15 rpm. The temperature difference between the inside and outside of the roller is to allow the molten adhesive to be adsorbed, solidified, and collected more quickly.
[0018] Furthermore, the porous ceramic roller has a pore size in the range of 5-15 micrometers and an open area ratio in the range of 25%-45%. The inner surface of the roller is coated with a zirconia coating, the weight of which accounts for 25%-45% of the weight of the porous ceramic roller. The outer surface of the roller is equipped with a scraper to remove the adhesive and prevent excessive surface adhesive from clogging the micropores. The pore size of the porous ceramic roller is smaller than the particle size of the black powder and the adhesive. If the open area ratio is higher than this range, the structural strength of the ceramic roller will decrease; if the open area ratio is lower than this range, the adsorption efficiency of the adhesive will decrease. The zirconia coating on the inner surface of the roller can reduce surface energy, increase strength, and increase the adsorption efficiency of the adhesive, but too much coating will increase cost.
[0019] Furthermore, the airflow separation utilizes a horizontal airflow separator to separate the black powder and the current collector based on their different densities (current collector aluminum foil: 2.7 g / cm³, black powder: 3.2 g / cm³) and particle sizes. The horizontal gas flow velocity is 4-6 m / s. The horizontal airflow separator is existing technology.
[0020] Beneficial technical effects: This invention sequentially processes waste lithium iron phosphate battery cathode sheets through liquid nitrogen low-temperature embrittlement and multi-stage mechanical sorting to form fine particles containing black powder, current collector aluminum foil, and binder. Subsequently, the PVDF binder is melted by pulsed hot air and captured by directional adsorption of the PVDF binder using a porous ceramic roller. Finally, airflow sorting yields the black powder and aluminum foil. This invention employs purely physical low-temperature separation, achieving efficient separation of black powder, aluminum foil, and binder by precisely controlling the mechanical properties and interfacial behavior of the materials, while avoiding chemical contamination and high-temperature damage. This provides a new technical path for the high-value recycling of waste lithium iron phosphate batteries.
[0021] This invention uses liquid nitrogen cryogenic freezing to embrittle PVDF, reducing its adhesive strength. This allows for mechanical dissociation with significantly lower energy consumption compared to conventional methods. Liquid nitrogen cryogenic freezing embrittlement solves the problem of incomplete separation caused by the high peeling force of PVDF at room temperature due to its high elasticity in traditional dry methods. Subsequently, hot air is used to melt the PVDF binder, which is then captured by directional adsorption using a porous ceramic roller. In the hot air environment, only PVDF is melted without damaging the black powder crystal structure, avoiding secondary pollution and resulting in high black powder purity. This solves the problems of toxic gases and damage to the lithium iron phosphate crystal structure produced by traditional high-temperature pyrolysis. After removing the binder, a horizontal airflow of 4-6 m / s is used for sorting, allowing the black powder and the current collector aluminum foil to be effectively separated due to their different settling velocities. This results in high separation efficiency and a final black powder product with a purity of over 99%. Attached Figure Description
[0022] Figure 1 This is a process flow diagram of the physical dry recycling method for waste lithium iron phosphate battery cathode sheets according to the present invention;
[0023] Figure 2 This is a schematic diagram of the structural device used in step S5 of the present invention, which employs pulsed hot air and porous ceramic rollers for adsorption and debinding. Detailed Implementation
[0024] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments and accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the present invention or its application or use. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] Unless otherwise specifically stated, the numerical values set forth in these embodiments do not limit the scope of the invention. Techniques and methods known to those skilled in the art may not be discussed in detail, but where appropriate, such techniques and methods should be considered part of the specification. In all examples shown and discussed herein, any specific values should be interpreted as merely exemplary and not as limitations. Therefore, other examples of exemplary embodiments may have different values. It should be noted that values expressed, for example, as "within the range of ab" or "between the range of ab," do not include the endpoint values a and b; values expressed as "for ab," "is ab," or "ab" include the endpoint values a and b.
[0026] Experimental methods not specified in the following examples are generally performed according to national standards; if there is no corresponding national standard, they are performed according to general standard requirements or general methods.
[0027] Example 1
[0028] The method for physical dry recycling of spent lithium iron phosphate battery cathode sheets includes the following steps:
[0029] S1. 300 kg of lithium iron phosphate battery electrode sheets from retired electric vehicles were selected. The average thickness was 0.24 mm, the LiFePO4 content was 66 wt%, the PVDF binder content was 9.5 wt%, the aluminum foil (current collector) content was 19 wt%, and the impurities and residual electrolyte accounted for 5.5 wt%. There was a small amount of edge curling on the electrode sheet.
[0030] Fragmentation process: The above lithium iron phosphate battery electrode sheets are cut into 5×5cm fragments, and then ferromagnetic impurities are removed by an electromagnetic sorting machine (magnetization intensity 5400GS) to form electrode fragments;
[0031] S2. Liquid nitrogen low-temperature embrittlement treatment: The electrode fragments are placed in a continuous liquid nitrogen embrittlement chamber and treated for 40 seconds at an ambient temperature of -47℃ and a pressure of 0.109MPa. Low-temperature freezing causes the PVDF to undergo a glass transition. After embrittlement, the peeling force is reduced, forming an embrittled electrode.
[0032] S3. Primary mechanical dissociation treatment: The embrittled electrode sheet is placed in a toothed disc crusher, the rotation speed is set to 750 rpm, and it is crushed to a particle size of less than 2 mm. The sieve passing rate is 98.3%, and granular electrode sheets are obtained.
[0033] Secondary mechanical dissociation treatment: The particle electrode is placed in a vortex mill and ground at 3400 rpm for 120 seconds to separate the black powder, aluminum foil, and binder, resulting in dissociated material;
[0034] S4. Two-stage sieving: The dissociated material is subjected to two-stage sieving to obtain oversize, intermediate, and undersize. The oversize consists of coarse agglomerated particles larger than 300 micrometers, which are returned to the vortex mill for recycling. The intermediate consists of aluminum current collector powder (separated) with a particle size of 200-300 micrometers. The undersize consists of fine black powder smaller than 50 micrometers, which mainly includes black powder, polymer binder, and trace current collectors, and proceeds to the next step of processing.
[0035] S5. Pulsed hot air debinding treatment: The fine black powder is fed into a hollow porous ceramic roller (the hollow inner surface has a zirconium oxide coating, the ZrO2 coating content accounts for 30% of the roller weight, the micropore diameter is 9μm, the micropores extend to the outside of the roller, the wall thickness is about 2mm, the porosity is 33%, the outer surface temperature of the roller is 185℃, and the rotation speed is 11rpm) through an airflow. The fine black powder is heated at the feed port end of the porous ceramic roller with pulsed hot air (pulsed hot air temperature 195℃, wind speed 17m / s). The pulsed hot air melts the PVDF in the fine black powder. The molten PVDF is then adsorbed to the outside of the roller by its micropores because its surface energy is close to that of the ceramic roller. A scraper is provided on the outer surface of the roller to scrape off the adhesive to prevent excessive surface adhesive from clogging the micropores. In this way, PVDF is removed and recovered. The PVDF removal rate is 99.85wt%, resulting in a mixture of black powder and current collector.
[0036] S6. Horizontal airflow separation: A horizontal airflow separator is used to perform horizontal airflow separation on the mixed materials. Under the action of multi-stage guide plates and a horizontal gas flow of 4.8 m / s, the black powder and the current collector aluminum foil are effectively separated in the airflow due to their different density and particle size differences, and the black powder product and current collector aluminum foil fragments are accurately separated.
[0037] Results: Black powder recovery rate 96.5 wt%, purity 99.5 wt%; aluminum foil recovery rate 97.5 wt%, purity 99.0 wt%.
[0038] Example 2
[0039] The method for physical dry recycling of spent lithium iron phosphate battery cathode sheets includes the following steps:
[0040] S1. Select 150kg of lithium iron phosphate battery electrode sheets discarded from energy storage cabinets. The average thickness is 0.22mm, the LiFePO4 content is 67wt%, the PVDF binder content is 8.5wt%, the aluminum foil content is 18.5wt%, the impurities and residual electrolyte account for 6wt%, and the surface corrosion of the electrode sheets is relatively light.
[0041] Fragmentation process: The above lithium iron phosphate battery electrode sheets are cut into 5×5cm fragments, and then ferromagnetic impurities are removed by an electromagnetic sorting machine (magnetization intensity 5400GS) to form electrode fragments;
[0042] S2. Liquid nitrogen low-temperature embrittlement treatment: The electrode fragments are placed in a continuous liquid nitrogen embrittlement chamber and treated for 50 seconds at an ambient temperature of -52℃ and a pressure of 0.111MPa. Low-temperature freezing causes the PVDF to undergo a glass transition, and the embrittlement reduces the peeling force, forming an embrittled electrode.
[0043] S3. Primary mechanical dissociation treatment: The embrittled electrode sheet is placed in a toothed disc crusher, the rotation speed is set to 850 rpm, and it is crushed to a particle size of less than 2 mm. The sieve passing rate is 98.6%, and granular electrode sheets are obtained.
[0044] Secondary mechanical dissociation treatment: The particle electrode is placed in a vortex mill and ground at 3600 rpm for 90 seconds to separate the black powder, aluminum foil, and binder, resulting in dissociated material;
[0045] S4. Two-stage sieving: The dissociated material is subjected to two-stage sieving to obtain oversize, intermediate, and undersize. The oversize consists of coarse agglomerated particles larger than 300 micrometers, which are returned to the vortex mill for recycling. The intermediate consists of aluminum current collector powder (separated) with a particle size of 200-300 micrometers. The undersize consists of fine black powder smaller than 50 micrometers, which mainly includes black powder, polymer binder, and trace current collectors, and proceeds to the next step of processing.
[0046] S5. Pulsed hot air debinding treatment: The fine black powder is fed into a hollow porous ceramic roller (the hollow inner surface has a zirconium oxide coating, the ZrO2 coating content accounts for 30% of the roller weight, the micropore diameter is 9μm, the micropores extend to the outside of the roller, the wall thickness is about 2mm, the porosity is 33%, the outer surface temperature of the roller is 185℃, and the rotation speed is 11rpm) through an airflow. The fine black powder is heated at the feed port end of the porous ceramic roller with pulsed hot air (pulsed hot air temperature 205℃, wind speed 19m / s). The pulsed hot air melts the PVDF in the fine black powder. The molten PVDF is then adsorbed to the outside of the roller by its micropores because its surface energy is close to that of the ceramic roller. A scraper is provided on the outer surface of the roller to remove the adhesive to prevent excessive surface adhesive from clogging the micropores. In this way, PVDF is removed and recovered. The PVDF removal rate is 99.92wt%, resulting in a mixture of black powder and current collector.
[0047] S6. Horizontal airflow separation: A horizontal airflow separator is used to perform horizontal airflow separation on the mixed materials. Under the action of multi-stage guide plates and a horizontal gas flow of 5.2 m / s, the black powder and the current collector aluminum foil are effectively separated in the airflow due to their different density and particle size differences, and the black powder product and current collector aluminum foil fragments are accurately separated.
[0048] Results: Black powder recovery rate 95.2 wt%, purity 99.8 wt%; aluminum foil recovery rate 98.2 wt%, purity 99.2 wt%.
[0049] Example 3
[0050] The recycling process in this case is the same as in Example 1, except that: the ambient temperature in S2 is -35℃; the speed of the toothed disc crusher in S3 is 1000 rpm, and the speed of the vortex mill is 3800 rpm; the ambient temperature of the hot air in S5 is 220℃, the surface temperature of the porous ceramic roller is 185℃, and the roller speed is 8 rpm; and the horizontal airflow velocity in S6 is 4.5 m / s.
[0051] Results: Black powder recovery rate 94.8 wt%, purity 99.3 wt%; aluminum foil recovery rate 97.8 wt%, purity 98.8 wt%.
[0052] Comparative Example 1
[0053] The recycling process in this case is the same as in Example 1, except that freezing and embrittlement were not performed.
[0054] Results: Black powder recovery rate 90.5 wt%, purity 96.9 wt%; aluminum foil recovery rate 94.6 wt%, purity 94.6 wt%.
[0055] Comparative Example 2
[0056] The recycling process in this case is the same as in Example 1, except that the S5 process was not performed, and the airflow was directly sorted according to the density difference.
[0057] Results: Black powder recovery rate was 96.5 wt%, purity was 94.8 wt%; aluminum foil recovery rate was 93.2 wt%, purity was 96.6 wt%.
[0058] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A method for physical dry recycling of waste lithium iron phosphate battery positive electrode sheets, characterized in that, Includes the following steps: S1. After fragmentation treatment of waste lithium iron phosphate battery positive electrode sheets, electromagnetic sorting is used to remove ferromagnetic impurities, forming electrode sheet fragments. S2. The electrode fragments are subjected to low-temperature embrittlement treatment to form embrittled electrode sheets; S3. Perform a primary mechanical dissociation treatment on the embrittled electrode sheet to obtain a particle electrode sheet with a particle size of less than 2 mm; Then, a two-stage mechanical dissociation process is carried out to obtain dissociated materials from black powder, current collector and polymer binder; S4. The dissociated material is subjected to two-stage sieving to obtain oversize, intermediate and undersize. The oversize consists of coarse agglomerated particles larger than 300 micrometers, and the undersize consists of fine black powder smaller than 50 micrometers. The fine black powder mainly includes black powder and polymer binder. The coarse particles are returned to the secondary mechanical dissociation process for recycling. S5. The fine black powder is fed into a hollow porous ceramic roller from one end by airflow, and the fine black powder is heated by pulsed hot air at the feed port end of the porous ceramic roller. The pulsed hot air melts the polymer binder in the fine black powder, and then the molten polymer binder is adsorbed to the outside of the roller by the micropores of the porous ceramic roller according to the surface energy difference. The micropores penetrate to the outside of the roller, thereby removing and recovering the polymer binder, and obtaining a mixture of black powder and current collector. S6. Perform airflow separation on the mixed materials to separate the black powder product and the current collector debris.
2. The method for physical dry recycling of waste lithium iron phosphate battery positive electrode sheets according to claim 1, characterized in that, The area of the electrode fragments does not exceed 25 cm². 2 The magnetic separation intensity of the electromagnetic separation is at least 2000 GS.
3. The method for physical dry recycling of waste lithium iron phosphate battery positive electrode sheets according to claim 1, characterized in that, The low-temperature embrittlement treatment is performed at ambient temperature of -25℃ to -60℃ and normal pressure for 30-60 seconds.
4. The method for physical dry recycling of waste lithium iron phosphate battery positive electrode sheets according to claim 1, characterized in that, The primary mechanical dissociation process employs a toothed disc crusher with a rotational speed ranging from 500 to 1500 rpm.
5. The method for physical dry recycling of waste lithium iron phosphate battery cathode sheets according to claim 4, characterized in that, The secondary mechanical dissociation process involves using a vortex mill to refine the particle electrode to a particle size of less than or equal to 300 micrometers; the mechanical rotation speed of the vortex mill is 2000-4000 rpm and the mechanical grinding time is 30-120 seconds.
6. The method for physical dry recycling of waste lithium iron phosphate battery positive electrode sheets according to claim 5, characterized in that, The polymeric binder is polyvinylidene fluoride; The temperature of the pulsed hot air is 190-220℃, and the wind speed is in the range of 10-30 m / s; The outer surface temperature of the porous ceramic roller is 160-185℃, and the roller speed of the porous ceramic roller is in the range of 5-15 rpm.
7. The method for physical dry recycling of waste lithium iron phosphate battery positive electrode sheets according to claim 6, characterized in that, The porous ceramic roller has a pore size in the range of 5-15 micrometers and an opening rate in the range of 25%-45%. The inner surface of the roller is coated with a zirconia coating, and the weight of the zirconia coating accounts for 25%-45% of the weight of the porous ceramic roller. The outer surface of the roller is equipped with a scraper.
8. The method for physical dry recycling of waste lithium iron phosphate battery positive electrode sheets according to any one of claims 1-7, characterized in that, The airflow separation is achieved by using a horizontal airflow separator to separate the black powder and the current collector based on their different densities and particle sizes. The horizontal gas flow velocity is 4-6 m / s.
Citation Information
Cited By
Waste lithium battery recycling method and recycling system
CN121198729A
Method and system for recycling waste lithium batteries
CN121198729B